Detection and Recognition of Fearful Facial Expressions During the Coronavirus Disease (COVID-19) Pandemic in an Italian Sample: An Online Experiment - Scarpina, Federica (Frontiers in Psychology, 2020)
In this observational study, the psychological ability to recognize the others’ fearful expressions in Italian individuals during the pandemic COVID-19 lockdown, was explored through a behavioral task performed online. An implicit version of the traditional facial emotion recognition task, grounded on the attentional and unconscious mechanism of the redundant target effect, was used. The experiment was script through the free software OpenSesame (Mathôt et al., 2012) and published on the Internet through the free software Jatos (Lange et al., 2015). The Reaction Time and level of Accuracy in detecting fearful expressions were computed. Overall, the data of 86 Italian individuals were collected. When their performance was scored in terms of Reaction Time, the redundant target effect did not emerge; instead, the expected effect was observed when the level of Accuracy was considered. Overall, the performance registered in this Italian sample in terms of accuracy was in line with previous results reported in Scarpina and colleagues (2018), in which a long extended version of the same behavioral task was used in a traditional experimental setting. This study might offer some considerations about the adoption of online experiments - together with self-report surveys - to assess the psychological and behavioral functioning during social restriction measures.